Erosion Surface and Pre-Cretaceous Inselbergs of the Western Margin of the Potiguar Basin – Northeastern Brazil - Lima, Thiago Rodrigues Sousa; Santos, Jader de Oliveira; Maia, Rúbson Pinheiro (Revista Brasileira de Geomorfologia, 2025)
The exhumation of inselbergs in the Potiguar Basin has revealed morphologies previously buried by Cretaceous sedimentation. These constitute granitic inselbergs formerly underlying the sedimentary rocks of the Apodi Group (Açu and Jandaíra Formations). This article aims to understand whether exhumed inselbergs in the western margin of the Potiguar Basin may serve as markers for the pre-Cretaceous geomorphological evolution in the studied area. Hypotheses were tested based on morphometric data combined with field collections for landscape interpretation. The results indicate that in the Cenozoic era, erosion of the western margin of the Potiguar Basin was intensified by the formation of the Jaguaribe River, which carved the valley and gave rise to the escarpment. With the migration of the main channel to the east, the escarpment underwent lateral retreat, revealing inselbergs, which are now situated within the valley, some even within the riverbed of the Jaguaribe River. These inselbergs might constitute the oldest granitic reliefs on Earth with respect to the overall granitic morphology. Their recent exhumation exposes a pre-Cretaceous erosion surface currently buried by the alluvium of the Jaguaribe River. This surface, along with the inselbergs, has been preserved since the Jurassic, as during the Cretaceous, the opening of the Atlantic and continental rifting allowed the formation of the Potiguar Basin.